STUDIES ON THE SUDANESE INDIGENOUS AFRICAN TOAD BUFO SPP. (Amphibia): PARTIAL CHARATERIZATION OF ANTIBACTERIAL PEPTIDES AND PROTEINS OF THE PARATOID GLAND - Abugabr, Husam Eldin Elhag; Elhussein, Salah Ahmed; Osman, Nour Ahmed; Mahmoud, Zuheir Nour-Eldaim (Gezira Journal of Health Sciences, 2007)
The parotoid gland secretion of Bufo spp., obtained by manual compression, was found to contain 23.1-41.2% (w/w) of total protein. Gel filtration chromatography showed the existence of four fractions of peptides and proteins responsible for antibacterial activity. Thin layer chromatography showed seven Ninhydrin-positive spots in addition to the origin, in the parotoid gland secretion of Bufo spp. Sodium Dodecyl Sulphate Polyacrylamide Gel Electrophoresis revealed the existence, in the crude secretion, of 2 bands of proteins (P1 and P2) and 2 bands of peptides (P3 and P4) with various molecular weights.